A model of work-integrated learning to prepare educational administrators for Thailand - Poungkaew, Phubet; Puthaprasert, Choocheep (Interdisciplinary Research Review, 2020)
This research aimed to 1) synthesize components of work-integrated learning, 2) investigate current conditions, problems, and factors supporting to success, and 3) develop and verify a model of work-integrated learning to prepare educational administrators for Thailand. Instruments used in this research were a component synthesis, an open-ended question, and a 5 rating-scale questionnaire. Data were analyzed by mean and standard deviation. Results of the research were found that the work-integrated learning consisted of 5 components. The current conditions were overall at a high level, problems were overall at a moderate level, and all factors supporting to success were overall at a high level, especially factors concerning curriculum and learners. The developed model of work-integrated learning was named ``POSO (ria) CDEM’’ model, consisting of 8 components. The model used for the development had the processes of developing knowledge and experiences to prepare educational administrators for Thailand consisted of 5 steps as follows: 1) creating basic knowledge, 2) practicing how to teach thinking, 3) bringing thinking skills to the classroom, 4) exchanging work reflections, and 5) organizing the sustainable work system. As regards the model verification, it was found all experts had verified the accuracy and suitability. Therefore, the developed model could be used as a master model to publish all over Thailand.